Effect of forest connectivity on the dispersal of species: A case study in the Bogda World Natural Heritage Site, Xinjiang, China. (June 2021) - Wang, Zhi; Yang, Zhaoping; Shi, Hui; Han, Lei
Highlights: Landscape fragmentation and connectivity of the Bogda forest, China, were assessed. Connectivity was high for long but low for short/medium distance dispersal species. Out of 196 habitat patches, two identified as integral for overall connectivity. Integral patches and small patches (dispersal 'stepping-stones') to be prioritized. Abstract: Habitat fragmentation hinders the dispersal of species and reduces the range of suitable habitat, thereby threatening the conservation of biodiversity. Even in protected areas, an assessment of the landscape connectivity of suitable habitat for species is still essential. In this paper, we investigated the overall forest connectivity, and determined patch characteristics and their role in species dispersion for species with different dispersal abilities in the World Natural Heritage Site of Bogda, Xinjiang, China. In our study site, the overall landscape connectivity was low for species with short- and medium-distance (≤500 m) dispersal, but high for species with long-distance (>500 m) dispersal abilities. We ranked the importance of patches according to their role in maintaining overall connectivity. Two patches were identified as being the most important: one mainly provided habitat area and fluxes (i.e., the flow of species into and out of the area) for species, while the other acted as a 'stepping-stone' for dispersal and provided fluxes. All species could use smaller patches (≤50 ha) as stepping-stones, and some of these patches could provide special environmental conditions for endemic species with short- and medium-distance dispersal abilities. Our study offers a way to prioritize the conservation of patches in a forest network for biodiversity and ecosystem health.